Moss diversity: New look at old numbers - Magill, R. E. (Phytotaxa, 2014)
Moss names published since 1801 and subsequently adjusted by monographic, floristic and molecular work provide a benchmark to review and estimate moss diversity. Information about these names is stored in the TROPICOS data base an on-line, interactive community resource. Nomenclatural data along with associated Web based floristic, monographic and bibliographic projects, provide one view of moss diversity based on the history of moss nomenclature and associated natural history information linked to the names.